Pengaruh Likuiditas Terhadap Kinerja Perusahaan Pada Perusahaan-Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2017-2019 - Nurul Rizki Anindita; Yefta Andi Kus Noegroho (Journal of Economic, Bussines and Accounting (COSTING), 2021)
Object of this research is manufacturing companies are listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The data used is secondary data, in the form of annual financing reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The data used in this research are secondary data, in the form of annual financial reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017. up to 2019. The purpose of this research is to determine whether the effect of current company liquidity is better in realizing company performance. This research used 194 manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sampling technique was purposive sampling which resulted in a total of 189 companies as the research sample. This analysis uses multiple regression analysis and the significant value of the t-test results of each variable. This research is a quantitative with data processing using Statistical Product and Service Solution (SPSS). The results of this research indicate that the liquidity variable has a significant effect on company performance and company size has an effect as a moderating variable on the relationship between liquidity and company performance. Keywords: Liquidity, Firm Performance, Firm Size